Pengaruh Komposisi Media Tanam Arang Sekam Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Varietas DxP Yangambi Pada Pre Nursery - Maulana, Taufan Yudia; Sugiono, Darso; Rahayu, Yayu Sri (JURNAL AGROPLASMA, 2023)
Oil palm is the largest vegetable oil-producing crop. With the increasing area of oil palm plantations, it is necessary efforts to improve the quality that affects production, one of which is the nursery. Topsoil as a commonly used planting medium is starting to be challenging to find, so an alternative planting medium is needed to replace topsoil. Charcoal husks can be used as a mixture of planting media. This study aims to obtain the best composition of rice husk charcoal and topsoil planting medium for the growth of oil palm seedlings (Elaeis guineensis Jacq.) of the Yangambi DxP variety during the pre-nursery period. This research was conducted at UNSIKA's new land, Pasirjengkol Village, Majalaya District, Karawang Regency. The design used was a single-factor Randomized Block Design (RBD) consisting of 4 treatments and 6 replications: M1 (100% topsoil), M2 (75% topsoil + 25% rice husk charcoal), M3 (50% topsoil + 50% rice husk charcoal) and M4 (75% top soil + 25% rice husk charcoal). Data were analyzed using F-test analysis at a 5% level. The results showed a significant effect of M3 treatment (50% top soil + 50% rice husk charcoal) on the number of leaves and M4 treatment (75% top soil + 25% rice husk charcoal) on root length. The M3 treatment (50% top soil + 50% husk charcoal) gave the best composition in the parameters of stem diameter, plant height, number of leaves, and leaf length, then the best root length parameters obtained by the M4 treatment (25% top soil + 75% charcoal husk).Â Keywords: growing medium, husk charcoal, nursery, Oil palm variety DxP Yangambi.